PENERAPAN ATURAN ASOSIASI DENGAN ALGORITMA APRIORI UNTUK MENGETAHUI POLA RESEP OBAT PADA PENYAKIT DIABETES MELITUS (Studi Kasus Rumah Sakit Umum Daerah Bangkinang) - Indra Irawan (RJOCS (Riau Journal of Computer Science), 2017)
The high number of diabetic patients who seek treatment at Bangkinang Public Hospital year by year, will have an impact on the increasing data entered in the database SIMRS. One of them is data about prescription drugs. Prescription drug data entered through inpatient, outpatient and hospital pharmacy is large-scale data. It is interesting to get a hidden pattern into invaluable information by using an association rule method with an a priori algorithm. With the discovery of a combination pattern of drugs prescribed by doctors to diabetic patients can make valuable sources of information, especially for doctors who deal with the disease.